Assessing the Effects of Al- Rasheed Electrical Power Plant on the Quality of Tigris River, Southern of Baghdad by Canadian Water Quality Index (CCME WQI) - Alazawii, Luma H.; Nashaat, Muhanned R.; Muftin, Fatema Sh. (Iraqi Journal of Science, 2018)
This study was conducted to investigate the effects of Al-Rasheed power plant (RPP) effluents at Al-Zafaraniya city on the physical – chemical of the Tigris River by using Canadian Water Quality Index(CCME WQI).Water samples were taken monthly at four positions and 11parameters were analyzed . The results of this study conducted that there was a significant impact of the RPP effluents on increase of water temperature, turbidity and electrical conductivity, and there was an increase in the phosphate concentration and water hardness at station 2 and the model classified water of Tigris river as poor in winter and fair to marginal in rest season for drinking and aquatic life